Cooperation between herpes simplex virus type 1-encoded ICP0 and Tat to support transcription of human immunodeficiency virus type 1 long terminal repeat in vivo can occur in the absence of the TAR binding site. - Schafer, S L (1996)
Expression of human immunodeficiency virus type 1 (HIV-1) provirus can be stimulated by herpes simplex virus type 1 (HSV-1) infection; the stimulation occurs at the level of transcriptional activation of the HIV long terminal repeat (LTR) and is mediated by both cellular and HSV-1-encoded transactivators. We have shown in this study that HSV-1 immediate-early gene ICP0 cooperates effectively with the HIV-1-encoded transactivator, Tat, in the stimulation of HIV-1 LTR-directed transcription. The cooperation between ICP0 and Tat is specific for the HIV-1 LTR and was not observed with other promoters (e.g., ICP0) that can be transactivated by ICP0 but not by Tat. Analyses of HIV-1 LTR deletion mutants have shown that ICP0 not only transactivates an HIV-1 LTR mutant that is unresponsive to NF-kappaB and Tat-mediated transactivation, such as the HIV-1 LTR with the enhancer deleted (-83 LTR) and TAR deleted (+20 to +81), but also restores responsiveness to Tat. ICP0 also showed cooperation with Gal4-Tat fusion protein-mediated transactivation of Gal4-HIV-1 LTR with TAR deleted. Enhancement of the transcriptional activation of ICP0 by Tat requires both the cysteine-rich and core domains of Tat and is inhibited by RO5-3335. ICP0 stimulates transcription of not only the HIV-1 LTR but also the TAR-defective HIV-1 provirus. We suggest that ICP0 can (i) recruit Tat to the vicinity of the HIV-1 promoter, thereby providing an alternative binding site for Tat, and (ii) substitute for the enhancer-binding proteins that are required for efficient Tat transactivation in T cells.